RETŲ SPAUDINIŲ KOMPLEKTAVIMAS LIETUVOS MOKSLŲ AKADEMIJOS VRUBLEVSKIŲ BIBLIOTEKOJE: PROBLEMOS, TRADICIJOS, PERSPEKTYVOS - NARBUTIENĖ, DAIVA (Knygotyra, 2011)
Lietuvos mokslų akademijos Vrublevskių biblioteka Žygimantų g. 1/8, LT-01102 Vilnius, Lietuva El. paštas: narbutiene@mab.lt Lietuvos mokslų akademijos Vrublevskių bibliotekos Retų spaudinių skyrius turi senas fondų komplektavimo tradicijas, syjančias su 1912 m. pradėjusia veikti Vilniaus advokato, bibliofilo Tado Vrublevskio (1858–1925) įkurtos bibliotekos formavimo raida. Specialusis raritetus komplektuojantis ir saugantis skyrius buvo įsteigtas 1957 m., sujungus tris – Senų, retų knygų, Meno leidinių ir Kartografijos leidinių – sektorius. Tai lėmė tolesnio dokumentų komplektavimo atrankos specifiką: čia saugomi ne tik seni ir reti spaudiniai, bet ir nauji meno bei kartografijos leidiniai. Lietuvos mokslų akademijos Vrublevskių bibliotekos Retų spaudinių skyriuje yra apie 400 tūkst. įvairaus pobūdžio dokumentų: knygų, periodinių leidinių, kartografinių spaudinių, meno albumų, raižinių, fotografijų, smulkiosios spaudos, mikrofilmų. Ši medžiaga sudaro atskirai suformuotus skyriaus fondus – rinkinius ir kolekcijas. Straipsnyje analizuojama, kaip Retų spaudinių skyriaus fondų turinys atitinka sąvokas „retas“ (raritetas) ir „cimelija“. Siekiama apibūdinti Retų spaudinių skyriaus komplektavimo turinį bei čia saugomų dokumentų atrankos specifiką. Taip pat norima prisiminti skyriaus fondų formavimo tradicijas ir nuspėti perspektyvas, leisiančias geriau ir racionaliau kaupti bei tvarkyti Retų spaudinių skyriaus dokumentus. Pagrindinis šaltinis – Retų spaudinių skyriaus darbo instrukcijos ir nuostatai. THE ACQUISITION OF RARE PUBLICATIONS IN THE WROBLEWSKI LIBRARY OF THE LITHUANIAN ACADEMY OF SCIENCES: PROBLEMS, TRADITIONS, PERSPECTIVES DAIVA NARBUTIENĖ Abstract The acquisition of rare publications has always been a challenge due to several factors. The first and foremost of them is the very concept of a rare publication, an issue that has been causing theoretical disputes for more than a decade. Another factor that influences the formation of special collections is the historical development of a specific library, shaped by the methods of obtaining documents. The structure of a library – the formation of its subdivisions – is also of importance. In addition to the above objective factors, there are also subjective aspects of work organization, such as the intellect and experience of the staff. Upon the merging of the sectors of Old and Rare Books, of Art and of Cartography, the Department of Old, Rare and Cartography Publications was founded in 1957. The character of the merged sectors was the main factor that determined the nature of the acquired documents, which has remained almost unchanged until today. In 1991, this department was divided into two: the departments of Old Periodicals and Rare Publications. The aim of this article is to characterize the acquisition strategy and the specifics of document selection in the Rare Book Department. Another objective is to overview the traditions of the formation of the department holdings and to outline the perspectives of a more effective keeping and cataloguing of documents. The main source is the Rules and Instructions for the work of the Rare Book Department. At present, the department operates on the basis of the Acquisition Instruction confirmed in 1996. The main principles of rare book acquisition are the following: age (pre-1801 publications), rarity (bibliographic rarities), value, uniqueness (exceptional documents whose preservation requires special conditions). The documents from the holdings of the Rare Book Department in the WLLAS electronic catalogue are labeled CIM (the abbreviation of “cimelia”, the word derived from the Greek κειμήλιον and meaning “treasure”). The Rare Book Department holds more than 200 thousand documents of various nature: books, cartography publications, art albums, engravings, photographs, small documents, microfilms. These materials are grouped into separately formed collections. Lately, the problem of the acquisition of newer documents (books, art albums, exhibition catalogues, accidental (small) documents) has become much more urgent. In our opinion, the Rare Book Department should accord more attention to printed heritage the concept of which is inseparable from a certain period in history.